SISTEM INFORMASI HASIL PENELITIAN RSUD WATES KULON PROGO - , FITO AJIPAMBUDI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
RSUD Wates is a general facility which has a function of not only health care but also as a center for science and the implementation of research conducted by various institutions, agencies, and from the university. The amount of research conducted made RSUD Wates required not only appropriate, but also fast in the management of research ever undertaken in RSUD Wates. Search within papers is very difficult and could takes a long time. Therefore, it is necessary to have an information system that can be used in the process of managing research results in RSUD Wates. Management can be done online to make it easier for employees to manage research. This system is developed using Code Igniter framework and MySQL database. Assessment of the system has been carried out by the head of the training and education division of RSUD Wates Kulon Progo. By looking at the assessment results, information system could facilitate research discovery in RSUD Wates Kulon Progo.